How to Rise to the Top...and Stay There! A Leadership Manual - Margulis, Alexander R.; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
The present dire economic environment has greatly affected business and the opportunities for advancement or even holding a job. Even universities, although not directly in business, are feeling the impact of diminishing endowments, resulting in lower disposable funds and reduction in innovative, unproven programs, which, in the past, often led to breakthroughs. These conditions we hope are only temporary, and they will not affect careers in the long run. This book is written to guide the reader on how to progress in his or her chosen career, how >to reach a high position in which one is actually in charge of a unit, department, school, or business and how to run it successfully.
Keywords: Education; Life sciences; Education; Learning & Instruction; Life Sciences, general; Administration, Organization and Leadership